Temnolopha paucusinota Muadsub & Pinkaew (Lepidoptera: Tortricidae: Olethreutinae), a new species from Thailand - Muadsub, Sopita; Pinkaew, Nantasak (Zootaxa, 2022)
Temnolopha paucusinota sp. nov. from Thailand is described as new to science. Two specimens, a male and a female were collected in Phu Kheio Wildlife Sanctuary, northeastern Thailand. Due to more complete wing pattern, the female specimen is selected as the holotype. Illustrations of adults and genitalia are provided. An identification key of Thai Temnolopha species is also provided. This new species increases the number of described Temnolopha species to five worldwide.